2011
DOI: 10.1161/circresaha.111.247304
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Endothelial Lineage Committed Genes in Pro-Angiogenic Hematopoietic and Endothelial Progenitor Cells

Abstract: Rationale: Proangiogenic hematopoietic and endothelial progenitor cells (EPCs) contribute to postnatal neovascularization, but the mechanisms regulating differentiation to the endothelial lineage are unclear.Objective: To elucidate the epigenetic control of endothelial gene expression in proangiogenic cells and EPCs. Methods and Results: Here we demonstrate that the endothelial nitric oxide synthase (eNOS) promoter is epigenetically silenced in proangiogenic cells (early EPCs), CD34؉ cells, and mesoangioblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 28 publications
3
87
1
4
Order By: Relevance
“…In humans with diabetic nephropathy, this coincided with upregulation in the expression of the demethylase UTX, whereas Jmjd3 levels were unaltered. This is interesting, because previous studies have suggested that Jmjd3 expression can be induced by stimuli such as hypoxia and inflammation, which are common features of CKD (9,44). Moreover, although UTX is considered to escape X chromosome inactivation (45), we did not detect a difference in podocyte UTX levels between male and female patients.…”
Section: Discussionmentioning
confidence: 46%
“…In humans with diabetic nephropathy, this coincided with upregulation in the expression of the demethylase UTX, whereas Jmjd3 levels were unaltered. This is interesting, because previous studies have suggested that Jmjd3 expression can be induced by stimuli such as hypoxia and inflammation, which are common features of CKD (9,44). Moreover, although UTX is considered to escape X chromosome inactivation (45), we did not detect a difference in podocyte UTX levels between male and female patients.…”
Section: Discussionmentioning
confidence: 46%
“…[11][12][13][14][15] DNA methylation and histone modifi cations also appear to be involved in the expression of eNOS during endothelial lineage commitment of early endothelial progenitor cells (EPCs). [16][17][18] For instance, the proximal region of the promoter (approximately 740 base pairs upstream from the main transcription start site) was shown to be heavily methylated in early EPCs but not in vascular endothelial cells, an interesting observation considering the role played by EPCs in the vascular phenotype among children with OSA. 19 In addition, repressive trimethyl histone H3 (Lys27) was enriched in the eNOS promoter in early EPCs and treatment with 3-deazaneplanocin A, an S-adenosylhomocysteine hydrolase inhibitor that inhibits Ezh2 and acts as an inhibitor of histone H3 (Lys27) trimethylation, and trichostatin A signifi cantly increased eNOS mRNA expression in these cells.…”
Section: Pyrosequencingmentioning
confidence: 99%
“…19 In addition, repressive trimethyl histone H3 (Lys27) was enriched in the eNOS promoter in early EPCs and treatment with 3-deazaneplanocin A, an S-adenosylhomocysteine hydrolase inhibitor that inhibits Ezh2 and acts as an inhibitor of histone H3 (Lys27) trimethylation, and trichostatin A signifi cantly increased eNOS mRNA expression in these cells. [16][17][18] Furthermore, the potential relevance of the methylation state of the eNOS gene has been recently explored in other contextual settings, such as obesity and bone mineral density. 20,21 In parallel, we have shown that pediatric OSA is associated with discrete increases in CpG site methylation in infl ammatory genes, particularly FOXP3 , suggesting that the presence of sleep-disordered breathing may be conducive to the presence of epigenetic alterations of selected genes.…”
Section: Pyrosequencingmentioning
confidence: 99%
“…Встановлено, що промотор eNOS здійс-нює епігенетичний контроль за модифікацією гістонів проангіогенних клітин [27]. Також вивчаються механізми пошкодження під впливом альдостерону гену мішені α-субоди-ниці епітеліального Na + -каналу (ENaC), що визначає зміни транскрипції [28].…”
Section: основні епігенетичні механізми розвитку артеріальної гіпертеunclassified